Energy discharge capability of surge arrester for 132 kV double circuit transmission line in Malaysia / Nor Hidayah Haji Nor Hassan - Norhidayah, Haji Nor Hassan (2018)
Lightning overvoltage has been identified as the major problem of overhead transmission lines tripping in Malaysia due to high incidence of keraunic activities. Improving lightning performance of the lines is crucial to avoid physical damage to the system equipment, which may result in service interruptions to the electricity consumers. Based on the studies conducted by the national utility company, application of surge arresters has been proven to be the most effective way in providing optimum lightning protection of a transmission line. Thus, in this work, the capability of surge arresters installed on a 132 kV double circuit transmission line in withstanding current and energy discharged by lightning strikes during back flashover phenomena is studied. Several surge arrester configurations and placement were simulated using Electromagnetic Transient Program (EMTP-RV) to determine the most effective protection design based on the actual tripping pattern recorded by Lightning Detection System (LDS) in Malaysia. Installing surge arresters at each phase conductor has been found to completely eliminate double circuit transmission line tripping due to back flashover. Some design parameters such as tower footing resistance, span length and phase conductor angle were varied to analyse their significance on the surge arrester discharged energy. The results indicate that increasing tower footing resistance, current magnitude and number of towers result in the surge arresters to discharge higher energy. It can be deduced that the designed surge arresters comply with the energy capability requirement of 5.1 kJ/kV as specified by the national utility company and are able to provide sufficient lightning protection on transmission lines.